Coating of electrospun poly(lactic‐co‐glycolic acid) nanofibers with willemite bioceramic: improvement of bone reconstruction in rat model. (6th June 2014) - Jamshidi Adegani, Fatemeh; Langroudi, Lida; Ardeshirylajimi, Abdolreza; Dinarvand, Peyman; Dodel, Masumeh; Doostmohammadi, Ali; Rahimian, Ali; Zohrabi, Parastoo; Seyedjafari, Ehsan; Soleimani, Masoud
Abstract We have investigated the combination effects of bioceramics and poly(lactide‐co‐glycolide) (PLGA) on bone reconstruction in calvarial critical size defects using a rat model. Willemite (Zn2SiO4) ceramics were prepared and coated on the surface of electrospun fabricated scaffolds. After scaffolds and nanoparticles characterization, osteoconductivity of the construct was analyzed using digital mammography, multislice spiral‐computed tomography (MSCT) imaging, and histological analysis. Eight weeks after implantation, no sign of inflammation was observed at the site of the osseous defect. The results showed that the ceramics supported bone regeneration and highest bone reconstruction were observed in willemite‐coated PLGA. This suggests that electrospun PLGA nanofibers coated with BG are potential candidate implants for bone tissue engineering applications.